The relation between leptin hormone and orthodotic alignment - Mustafa Al-Ahmad, Basma Ezzat (2020)
During orthodontic tooth movement, the early response of periodontal tissues to mechanical stress is an acute inflammatory reaction. Mechanical stress from orthodontic appliances is believed to induce cells in the periodontal ligament (PDL) to form biologically active substances, such as enzymes and cytokines, responsible for connective tissue remodeling. Leptin, a polypeptide hormone has been classified as a cytokine. Earlier findings concluded that leptin at high local concentrations protects the host from inflammation and infection as well as maintaining bone level. It has been also suggested that leptin plays a significant role in bone formation by its direct effect on osteoblast. Leptin in saliva shows high association with tooth movement during initial orthodontic alignment stage.